Cultural and artistic societies in the western Ukrainian lands (1920s–1930s): the historical experience and future prospects of cultural analysis - Pavlichenko, Bogdan; Vdovychenko, Heorhii (Ukrainian Cultural Studies, 2025)
Background. Cultural and artistic societies played an important role in the processes of Ukrainian cultural, national, and state formation from the 19th century to the mid-20th century. Alongside the well-known “Prosvita” and the Shevchenko Scientific Society, the revival of Ukrainian statehood in the 20th century rested on the activities of a wide range of literary and artistic societies. During the Polish, Czechoslovak, and Romanian rule over the Western Ukrainian lands in the interwar period of the 1910s–1930s, these societies made significant contributions to the institutionalization of Ukrainian culture. The purpose of this research is to analyze and systematize how cultural and artistic societies in interwar Eastern Halychyna, Western Volyn, Northern Bukovyna, and Transcarpathia have been culturally analyzed from the 1930s to the present day.Methods. To achieve this goal, both classical and contemporary methods of cultural analysis, along with the core principles of scientific inquiry–such as consistency, objectivity, and historicism–were employed.Results. Publications on cultural societies in the Western Ukrainian lands during the interwar period can be classified into three main groups. The first group includes sources that document the history of these societies and their founders, and evaluate their contribution to the institutionalization of Ukrainian cultural life (e.g., History of Ukrainian Culture, 1937; Narizhny, 1942). The second group presents politically controversial perspectives on these societies from scholars in Western democracies and the Ukrainian SSR in the second half of the 20th century. Systematic analysis of the history of these societies began only in the 1990s, primarily through the initiation of their cultural analysis at the NASU and in Ukrainian universities.Conclusions. It has been established that two groups of authors behind the monographs “History of Ukrainian Culture” (1937), led by I. Krypyakevych, and “Ukrainian Culture” (1940), led by D. Antonovych, served as key centers for the study of these societies. Many of their contributors–such as M. Holubets, V. Sichynsky, and S. Charnetsky–were themselves founders of these organizations. The first general analysis of these societies, presented by Narizhny (1942), like their very history, was falsified and suppressed in the Ukrainian SSR. Unbiased study of the topic by domestic scholars began only in the 1990s, based on archival sources and the scholarly legacy of the Ukrainian diaspora. A particularly promising aspect in this intellectual context is the reinterpretation of the history of these societies within the frameworks of Postmodern and emerging Metamodern Cultural Studies, as applied at the National Academy of Sciences of Ukraine and Ukrainian universities.
Keywords: Ukrainian culture of the 20th century; Interwar stage; Eastern Halychyna; Western Volyn; Northern Bukovyna; Transcarpathia; cultural and artistic societies in Western Ukraine in the 1920s and 1930s; D. Antonovych; I. Krypyakevych